CT-guided percutaneous aspiration and bleomycin sclerotherapy for symptomatic hepatic cysts: technique and three-year outcomes - Li, Long; Lao, Yong-Hao; Han, Qiang-Lin (Frontiers in Medicine, 2025)
ObjectiveWe aimed to evaluate the long-term efficacy and safety of CT-guided percutaneous aspiration and bleomycin sclerotherapy for symptomatic hepatic cysts at a minimum follow-up of 3 years.Materials and methodsMedical records of patients who underwent CT-guided percutaneous aspiration and bleomycin sclerotherapy for large (>5 cm) symptomatic simple hepatic cysts and polycystic liver disease were reviewed retrospectively. The choice of percutaneous needle or catheter aspiration was based on the estimated cyst volume. The administered dose of bleomycin was calculated at 5 mg per 100 mL of cyst fluid, with a maximum dose not exceeding 0.6–0.8 mg/kg of body weight per patient. Clinical outcomes, including symptom relief evaluated by the Chronic Liver Disease Questionnaire and the technical response defined by the cyst volume reduction rate, were assessed at 6-, 12-, 24-, and 36-month follow-ups post-sclerotherapy.ResultsA total of 96 cysts in 88 patients (mean age 61.8 ± 18.2 years; 56.8% female) were treated with single-session percutaneous aspiration and bleomycin sclerotherapy. Of these, 81 patients had symptomatic simple hepatic cysts, while 7 had polycystic liver disease. The total bleomycin dose administered ranged from 10 mg to 50 mg per patient, with a median dose of 41.0 mg. All patients reported significant symptom relief, with 81 patients (92.0%) experiencing complete symptom resolution and 7 patients (8.0%) with polycystic liver disease showing improvement from 12 months to 36 months post-procedure. The overall response rates at 6, 12, 24, and 36 months were 96.9% (93 of 96), 100% (96 of 96), 100% (96 of 96), and 100% (96 of 96), respectively. No major complications or bleomycin-related toxicities were observed during or after the procedure.ConclusionCT-guided single-session percutaneous aspiration and bleomycin sclerotherapy is an effective and safe treatment for symptomatic simple hepatic cysts and polycystic liver disease.